Examining longer-term effects of parental death in adolescents and young adults: Evidence from the national longitudinal survey of adolescent to adult health. Issue 3 (16th March 2017) - Feigelman, William; Rosen, Zohn; Joiner, Thomas; Silva, Caroline; Mueller, Anna S.
ABSTRACT: Using longitudinal data spanning a 7-year period, we investigated the behavioral and psycho-social effects resulting from a parent's death during early childhood or teenage years on adolescent and early adulthood functioning. Findings confirmed previous work demonstrating various behavioral problems and social-psychological adjustment deficits during adolescence. Results suggested that most detrimental adjustment behaviors among parentally bereaved youth fade as they entered into young adulthood. Yet, premature school withdrawals and diminished interests in college attendance at Wave 1 left many of these young adults with diminished academic accomplishments, lingering economic disadvantages and for females a hesitancy to marry as their lives progressed into adulthood.